Dora's box - Campbell, Ann.; Negrin, Fabian (New York : Knopf, 1998)
In order to protect her, Dora's parents put anything that might frighten or hurt her into a box and tell her never to open it, but when she eventually does, her life is enriched by what she finds.
5.2
K-3
Elem. School Library Collection
Publisher's Weekly
Booklist
Keywords: Empathy -- Fiction; Emotions -- Fiction; Parent and child -- Fiction; Empathy -- Fiction; Emotions -- Fiction; Parent-child relationship -- Fiction